Approaching the isotropic spin-ladder regime: structure and magnetism of all-pyrazine-bridged copper(ii)-based antiferromagnetic ladders. Issue 12 (25th February 2022) - Monroe, Jeffrey C.; Carvajal, M. Angels; Landee, Christopher P.; Deumal, Mercè; Turnbull, Mark M.; Wikaira, Jan L.; Dawe, Louise N.
Abstract : Cu(ii )-Based magnetic ladders catena -([Cu(pz)1.5 (L)2 ](ClO4 )2 (L = 3-X-4-pyridone) been prepared and characterized. Calculations support the proximity to the isotropic magnetic-ladder regime. Abstract : The crystal structure and magnetic properties of two all-pyrazine-bridged antiferromagnetic spin ladders are reported. The complexes, catena -(bis(3-X-4-pyridone)(μ-pyrazine)copper(ii )(-μ-pyrazine)diperchlorate ([Cu(pz)1.5 (L)2 ](ClO4 )2 where L = 3-X-4-pyridone and X = Br (1 ) or Cl (2 )), contain copper(ii )-based ladders in which both the rung and rail bridges are pyrazine molecules bonded through the x 2 – y 2 orbital of the copper(ii ) ions. This structural scaffold is proposed to approach the isotropic spin-ladder regime. 1 and 2 crystallize in the monoclinic space group P 21 / c . Due to the bulk of the 3-X-4-HOpy ligands, the ladders are well isolated in the a -direction (1, 15.6 Å; 2, 15.5 Å). The ladders, which run in the b -direction, are stacked in the c -direction with the separation (1, 7.87 Å; 2, 7.82 Å) between copper(ii ) ions caused by the bulk of a semi-coordinate perchlorate ion coordinated in the axial position. Computational evaluation of magnetic J AB couplings between Cu-moieties of 2 supports the experimentally proposed magnetic topology and agrees with an isolated isotropic spin-ladder ( J rail = −4.04 cm −1 (−5.77 K) and J rung = −3.89 cm −1 (−5.56 K)). These complexes introduce a convenient scaffold for synthesizing isotropic spin-ladders with modest superexchange interactions, the strength of which may be tuned by variations in L. The magnetic susceptibility down to 1.8 K, for both compounds, is well described by the strong-rung ladder model giving nearly isotropic exchange with J rung ≈ J rail ≈ −5.5 K (1 ) and −5.9 K (2 ) using the Hamiltonian. Theoretical simulations of the magnetic response of 2 using the isotropic ladder model are in excellent agreement with experiment. The measured magnetization to 5 T indicates a quantum-dominated magnetic spectrum. Again, calculated lower and saturation (4.3 and 24 T, respectively) critical fields for 2 are consistent with experimental measurements, and magnetization data at very low temperatures indeed suggest the presence of quantum effects. Further, the computational study of short- and long-range spin ordering indicates that a 2D-to-3D crossover might be feasible at lower temperatures. Analysis of the Boltzmann population corroborates the presence of accessible triplet states above the singlet ground state enabling the aforementioned 2D-to-3D crossover.